Concise Review: Cell Therapies for Hereditary Metabolic Liver Diseases—Concepts, Clinical Results, and Future Developments. (24th March 2015) - Cantz, Tobias; Sharma, Amar Deep; Ott, Michael
Abstract: The concept of cell-based therapies for inherited metabolic liver diseases has been introduced for now more than 40 years in animal experiments, but controlled clinical data in humans are still not available. In the era of dynamic developments in stem cell science, the "right" cell for transplantation is considered as an important key for successful treatment. Do we aim to transplant mature hepatocytes or do we consider the liver as a stem/progenitor-driven organ and replenish the diseased liver with genetically normal stem/progenitor cells? Although conflicting results from cell tracing and transplantation experiments have recently emerged about the existence and role of stem/progenitor cells in the liver, their overall contribution to parenchymal cell homeostasis and tissue repair is limited. Accordingly, engraftment and repopulation efficacies of extrahepatic and liver-derived stem/progenitor cell types are considered to be lower compared to mature hepatocytes. On the basis of these results, we will discuss the current clinical cell transplantation programs for inherited metabolic liver diseases and future developments in liver cell therapy. Stem Cells   2015;33:1055–1062